Synaptic Signaling and Aberrant RNA Splicing in Autism Spectrum Disorders - Smith, Ryan M.; Sadee, Wolfgang (Frontiers in Synaptic Neuroscience, 2011)
Interactions between presynaptic and postsynaptic cellular adhesion molecules drive synapse maturation during development. These trans-synaptic interactions are regulated by alternative splicing of cellular adhesion molecule RNAs, which ultimately determines neurotransmitter phenotype. The diverse assortment of RNAs produced by alternative splicing generates countless protein isoforms necessary for guiding specialized cell-to-cell connectivity. Failure to generate the appropriate synaptic adhesion proteins is associated with disrupted glutamatergic and gamma-aminobutyric acid signaling, resulting in loss of activity-dependent neuronal plasticity, and risk for developmental disorders, including autism. While the majority of genetic mutations currently linked to autism are rare variants that change the protein coding sequence of synaptic candidate genes, regulatory polymorphisms affecting constitutive and alternative splicing have emerged as risk factors in numerous other diseases, accounting for an estimated 40-60% of general disease risk. Here, we review the relationship between aberrant RNA splicing of synapse-related genes and autism spectrum disorders.